The financial ombudsman scheme as am alternative dispute resolution mechanism for financial disputes: The Malaysian experience - Syed A Rahman, Syed Fadhil Hanafi; Mokhtar, Khairil Azmin (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
Evils in litigation have led disputing parties to prefer settlement of conflicts via alternative dispute resolution. The evils include lengthy processes, time consuming, expensive cost, stringent and technical procedures, as well as offensive in nature which ruins cordial relationships between litigants. However, the increased use of alternative dispute resolution especially arbitration and active involvement of legal practitioners in its procedures had caused arbitration to be infected with the same disease like litigations making it not much appealing as it used to be. Hence, people has moved towards using other forms of alternative disputes resolution mechanisms. To encourage the use of alternative dispute resolutions, authorities in various jurisdictions have taken numerous measures to invest it with attractive benefits. In Malaysia, Bank Negara Malaysia as an authority for the financial sector initiated the financial ombudsman scheme to be the preferred, statutory sanctioned alternative dispute resolution mechanism for financial disputes with various incentives. Among the incentives are it is free of charge, speedy and does not require representation by legal practitioner. In this paper, we discuss the history of the financial ombudsman scheme, its purposes, processes and benefits to financial consumers as well as criticisms and suggestions for improvement of the scheme.